Prospective randomized trial of neoadjuvant chemotherapy during the 'wait period' following preoperative chemoradiotherapy for rectal cancer: results of the WAIT trial. (1st November 2017) - Moore, J.; Price, T.; Carruthers, S.; Selva‐Nayagam, S.; Luck, A.; Thomas, M.; Hewett, P.
Abstract: Aim: The aim was to determine whether the addition of additional cycles of chemotherapy during the 'wait period' following neoadjuvant chemoradiotherapy for rectal cancer improves the pathological complete response (pCR) rate. Method: Rectal cancer patients were randomly allocated either to a standard 10 week wait period before surgery (standard chemoradiotherapy, SCRT) or to receive three cycles of fluorouracil based chemotherapy following chemoradiotherapy during a similar 10 week wait (extended chemoradiotherapy, XCRT). The primary end‐point was pCR as determined by blinded pathological assessment. Results: Forty‐nine patients were randomized (SCRT n = 24, XCRT n = 25). pCR occurred in 10 patients overall but there was no significant difference in pCR between the groups (SCRT n = 6, XCRT n = 4, P = 0.49). Conclusion: The addition of three cycles of 5‐fluorouracil/leucovorin in a 10 week wait period after conventional chemoradiotherapy seems to result in similar pCR rates in patients with locally advanced rectal cancer based on this small randomized trial.